2013
DOI: 10.1590/s1516-18462013005000014
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de rinite, respiração oral e alterações orofaciais em adolescentes asmáticos

Abstract: OBJETIVO: determinar a ocorrência de rinite, respiração oral e alterações orofaciais em adolescentes asmáticos. MÉTODO: estudo do tipo transversal, realizado com 155 adolescentes asmáticos de 12 a 15 anos e de ambos os sexos, atendidos no Instituto Materno Infantil Professor Fernando Figueira. O levantamento de dados consistiu de duas etapas: a primeira para análise dos prontuários dos pacientes e da realização de dois testes para avaliação adicional da função respiratória. Sendo um com o auxílio do espelho de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…The relationship between asthma and rhinitis does not seem to be fully established, since both disorders may represent two distinct entities or a disease involving both airways 17 . Chaves et al 26 reported that the association between both diseases can lead to the development of a series of postural changes and in the primary and accessory muscles of inspiration.…”
Section: Implications Of Mouth Breathing For the Pulmonary Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between asthma and rhinitis does not seem to be fully established, since both disorders may represent two distinct entities or a disease involving both airways 17 . Chaves et al 26 reported that the association between both diseases can lead to the development of a series of postural changes and in the primary and accessory muscles of inspiration.…”
Section: Implications Of Mouth Breathing For the Pulmonary Functionmentioning
confidence: 99%
“…Mouth breathing may be associated with genetic factors, inadequate oral habits (pacifier and finger sucking, baby bottle) and nasal obstruction with variable intensity and duration 7 . Rhinitis is one of the main causes of nasal obstruction with a high prevalence in the population 17 . Mouth breathing in children is a frequent complaint in the pediatrician, allergist and otorhinolaryngologist's practice 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Teething is a natural and physiological process and should not cause any problem except mild fever and pain due to the inflammation. 20 Menezes et al 21 in their study revealed that events such as recurrent allergies and asthma cause nasal obstructions and favor mouth breathing; they are therefore considered predisposing factors for malocclusion; 88.67% of the pediatricians participated in the study were well aware about this fact, while 7.54% answered no and 3.77% did not comment to this…”
Section: Results Discussionmentioning
confidence: 99%
“…Sabe-se que a presença da mordida aberta pode dificultar o vedamento labial e favorecer a presença da respiração bucal 20 . Em um estudo prévio, Menezes et al 21 (2006) avaliaram indivíduos portadores de respiração bucal, e os maiores percentuais verificados relacionados a alterações faciais foram para a presença de mordida aberta anterior (60%), selamento labial inadequado (58,8%) e palato ogival (38,8%) 21 . No presente estudo, foi observada uma associação entre maloclusão e atopia (p=0,044), em que o grupo alérgico apresentou uma frequência menor de maloclusões quando comparado ao grupo não alérgico (12,24% e 22,9%, respectivamente).…”
Section: Discussionunclassified